FAMILY FACTORS RELATED TO 4T PREGNANCY AT UPTD PUSKESMAS UBUNG IN 2024 - Wardani, Putu Ayu Agustina Eka; Apriani, Lia Arian; Sustiyani, Elly; Agustiarini, Anastasya (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2026)
4T pregnancy defined as pregnancy occurring at too young an age (under 20 years), too old (over 35 years), too many children, or with birth intervals that are too close—remains a significant contributor to maternal and neonatal complications. This study aimed to analyze family-related factors associated with 4T pregnancy at UPTD Puskesmas Ubung, Central Lombok, Indonesia, in 2024. A quantitative cross-sectional design was employed using primary data collected through structured questionnaires and guided interviews. The study population consisted of all pregnant women attending antenatal care services at UPTD Puskesmas Ubung in 2024 (N = 108). A total of 85 respondents were selected using purposive sampling based on predefined inclusion and exclusion criteria. Data were analyzed using univariate analysis and chi-square tests with a significance level of α = 0.05. The results indicated that multiparous mothers (p = 0.047), working mothers (p = 0.023), and mothers within the ideal reproductive age (20–35 years) (p = 0.0001) had a significantly lower risk of 4T pregnancy. In addition, good family knowledge (p = 0.034) and strong family support (p = 0.015) were significantly associated with a reduced risk of 4T pregnancy. This study concludes that family factors play a crucial role in mitigating the risk of 4T pregnancy. Future interventions should prioritize family-based reproductive health education and further longitudinal studies are recommended to explore causal relationships between family factors and high-risk pregnancy outcomes.